2015
DOI: 10.1007/s12149-015-1020-4
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between the metabolic tumor volume and hematological parameters in patients with esophageal cancer

Abstract: At baseline neutrophil-to-lymphocyte ratio is associated with the metabolic tumor volume, which was assessed using the PET/CT in patients with esophageal squamous cell cancer. The SUVmax values were not related to these parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…A weak but statistically significant correlation was found between SUVmax and NLR. Furthermore, several studies have demonstrated a direct association between metabolic tumor volume (MTV) and NLR [34][35][36]. In our present study, we determined that SUVmean also had a positive correlation with NLR.…”
Section: Discussionsupporting
confidence: 51%
“…A weak but statistically significant correlation was found between SUVmax and NLR. Furthermore, several studies have demonstrated a direct association between metabolic tumor volume (MTV) and NLR [34][35][36]. In our present study, we determined that SUVmean also had a positive correlation with NLR.…”
Section: Discussionsupporting
confidence: 51%
“…If such correlations exist, PET parameters and hematological parameters may provide complementary information that could be combined for prognosis assessment. To the best of our knowledge, while several reports (21,22) have explored how PET parameters are correlated with NLR and PLR, no reports have addressed this topic for LACC. Therefore, this study was conducted for the following purposes: (I) to compare the values of SUV max , MTV, and TLG of the primary tumor (SUV max -P, MTV-P, and TLG-P, respectively) and the combination of the primary tumor and SMLNs (SUV max -C, MTV-C, and TLG-C, respectively) based on different percentages of SUV max (%SUV max ) thresholds for evaluating tumor recurrence and find the optimal PET parameter; (II) to investigate correlations between PET parameters and hematological parameters to determine the most relevant PET parameters and optimal thresholds; (III) and to explore independent risk factors affecting recurrence-free survival (RFS) for LACC.…”
Section: Introductionmentioning
confidence: 99%
“…Several markers in the complete blood counts including the neutrophil-tolymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and mean platelet volume (MPV) have been studied in several cancer types and inflammatory conditions [6,7,11,12]. The NLR has been significantly correlated with the size of tumor and higher NLR may imply a poorer tumor profile in well-DTC [13,14].…”
Section: Introductionmentioning
confidence: 99%